North Sea formation waters atlas - Warren,EA; Smalley,PC (North Sea Formation Waters Atlas, 1994)
This atlas provides data on formation water compositions from throughout the North Sea Basin. The objective was not simply to provide a table of water compositions, but to supply as much supplementary data on reservoir conditions and geological setting as possible to enable the individual data to be placed in context. The atlas contains four main sections: a field compendium, comprising a field-by-field compilation of water compositions with accompanying geological description and field maps; a water resistivity (Rw) atlas; scale prediction maps estimating susceptibility of produced waters to scaling; and a water chemistry atlas. -from Editors